The Ecological ICMS as Inducer in the Creation of Protected Areas in Brazil: An Assessment of Policy in the States of Pernambuco, Paraná and Bahia - Luiz Honorato da Silva Júnior (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
The main objective of this paper is to evaluate the effectiveness of the ecological ICMS to induce the creation of conservation units in Brazil, by analyzing the results of this policy in the municipalities of the Brazilian states of Paraná, Pernambuco and Bahia. The average effect of treatment as empirical strategy was used for that purpose. This study has showed that the stage of development and population size of cities is important to explain the dynamics of protected areas. The Ecological ICMS in Paraná was found to present better results than those observed in Pernambuco, that the policy in this state can be a model for Bahia and other states wanting to implement such a policy.